Comparison of the Effectiveness of Biomedical Subject Learning Methods - Syokumawena; Herawati Jaya (Yayasan Rumah Ilmu Professor, 2022)
The Covid-19 outbreak requires the teaching and learning process to change to using online methods. The purpose of this study was to determine the evaluation of student learning in basic biomedical science courses consisting of theory and practicum with offline and online methods by looking at the scores of students' final semester exam results.The sample for this assessment is 174. The value of offline theory compared to online differs by 4.94 points, where the online value is high. The value of online practicum learning compared to offline is 8.2 points different, where the online value is also higher. Final semester test scoresmethod theoryoffline varies from 43 – 88 whilemethodonline from the value of 52 – 92. The results of the final semester practicum exam scoresmethodoffline from 68 - 90 while online ranging from 60 - 98. The average percentage of online theory learning methods is 74.15andthe average offline theory learning method is 69.21. Meanwhile, the average percentage of offline practicum learning methods is 74.59 and the average percentage of online practicum learning methods is 82.79. The analysis of this research uses the SPSS program independent samples t-test with the results of the value of️= 4.818and siq of 0.013 (less than 0.05), then the conclusion is the result of the value of basic biomedical science with online learning methods is higher than offline learning.